The Sensitivity of Secondary Sovereign Loan Market Returns to Macroeconomlc Fundamentals. (IMF Working Papers; Working Paper ;, 1990)
The sensitivity of secondary sovereign loan market returns to three classes of economic news is estimated in the arbitrage pricing theory framework. Returns are characterized by a limited response to unexpected changes in procyclical U.S. aggregates. Shocks to country-specific balance of payment indicators do not impact debt prices. Announcements of policy changes by creditors and third parties that presage changes in future lending induce large debt price changes. The failure of the data to meet the empirical arbitrage pricing theory restrictions and the large proportion of return variance unexplained by macroeconomic fundamentals highlight the differences between corporate and sovereign securities.